2017
DOI: 10.1021/acssuschemeng.6b02724
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Computer-Aided Process Simulation and Estimations of Emissions and Land Use for Rapid Life Cycle Inventory Modeling

Abstract: A methodology is described for developing a gate-to-gate life cycle inventory (LCI) of a chemical manufacturing process to support the application of life cycle assessment in the design and regulation of sustainable chemicals. The inventories were derived by first applying process design and simulation to develop a process flow diagram describing the energy and basic material flows of the system. Additional techniques developed by the United States Environmental Protection Agency for estimating uncontrolled em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…More recent approaches are based on advanced process calculations (65,66) and data mining (67). Parvatker & Eckelman (44) compared these prediction methods for LCI.…”
Section: Data Sources For Background Systemsmentioning
confidence: 99%
“…More recent approaches are based on advanced process calculations (65,66) and data mining (67). Parvatker & Eckelman (44) compared these prediction methods for LCI.…”
Section: Data Sources For Background Systemsmentioning
confidence: 99%
“…Where necessary, end-of-pipe treatment needs to be applied to such streams. 56 Smith et al 51 showed how simulations can be improved with vent, storage, and fugitive emission models. This work provides spreadsheet tools for storage and fugitive emission calculations and on-site utility generation.…”
Section: Methodsmentioning
confidence: 99%
“…This work is interesting because the authors developed methods to model ancillary energy processes (JimĂ©nez‐GonzĂĄlez, 2000b) separate from the chemical of interest (JimĂ©nez‐GonzĂĄlez et al., 2000a). Numerous other examples of using process design in LCI modeling have followed (Alvarado et al., 2019; Geisler, Hofstetter, & HungerbĂŒhler, 2004; Parvatker et al., 2019; Simon et al., 2019; Yao, 2018), with this approach eventually expanding to include full process simulation (Liao, Kelley, & Yao, 2020; Smith et al., 2017). Although effective, process design and simulation often require detailed process knowledge and chemical engineering expertise that may not be practical or readily available (Meyer et al., 2019; Parvatker, 2018).…”
Section: Introductionmentioning
confidence: 99%